A CASE REPORT ON ROLE OF N-ACETYLCYSTEINE IN NON–ACETAMINOPHEN RELATED ACUTE LIVER INJURY - Thampi, Anooja (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Â Acute liver failure is a clinical entity associated with a high mortality rate and majority of these patients may require liver transplantation. N-Acetylcysteine (NAC), an antioxidant agent that replenishes mitochondrial and cytosolic glutathione stores, is an antidote for acetaminophen poisoning. But their role in nonâ€“acetaminophen-related acute liver failure is still not proven. Here, we discuss about a 67 year old male patient diagnosed with hepatitis with acute liver injury who was admitted in Emergency Medicine. He was treated with N- Acetylcysteine infusion for an average of 48 hours and later it was found that his liver function tests improved. In this study, we could find that N-Acetylcysteine plays a major role in improving the liver function test of patients with nonâ€“acetaminophen-related acute liver failure.